Improving the Catalytic Performance of Pectate Lyase Through Pectate Lyase/Cu3(PO4)2 Hybrid Nanoflowers as an Immobilized Enzyme - Wu, Pan; Luo, Feifan; Lu, Zhenghui; Zhan, Zhichun; Zhang, Guimin (Frontiers in Bioengineering and Biotechnology, 2020)
Pectate lyases (Pels) can be used in the textile industrial process for cotton scouring and ramie degumming, and its hydrolyzed products -oligo galacturonic acid, are high-value added agricultural and health products. In our previous studies, an alkaline pectate lyase PEL168 mutant, PEL3, was obtained with improved specific activity and thermostability. Here, a facile and rapid method of preparing an immobilized PEL3-inorganic hybrid nanoflower was developed to improve its biocatalytic performance. , were used as inorganic component. The results showed that PEL3/Cu3(PO4)2 hybrid nanoflowers presented the highest activity with a nearly 2.5-fold increase comparing to the free PEL3. XRD analysis proved that the prepared PEL3/Cu3(PO4)2 hybrid nanoflowers were formed by pectate lyase PEL3 and Cu3(PO4)2· 5H2O. The optimum temperature and pH of PEL3/Cu3(PO4)2 hybrid nanoflowers were ascertained to be 55 ℃ and pH 9.0, respectively, exhibiting subtle difference from the free PEL3. However, the PEL3/Cu3(PO4)2 hybrid nanoflowers maintained 33% residual activity after 24 h incubation at 55 ℃, while the free PEL3 completely lost its activity after 18 h incubation at 55 ℃. Furthermore, over 50 % residual activity of the PEL3/ Cu3(PO4)2 hybrid nanoflowers was remained, even after four times of repetitive utilization, demonstrating its promising stability for practical application.